Exploration of Potential Endophytic Fungi from Ironwood (Eusideroxylon zwageri Teijsm. & Binn.) as an Antibacterial Agent - Iffat Raihana; Witiyasti Imaningsih; Nashrul Wathan (Universitas Atma Jaya Yogyakarta, 2026)
This study investigates the endophytic fungi found in ironwood (Eusideroxylon zwageri T et. B), a plant valued by the Kalimantan community for its medicinal uses, especially in treating rheumatism and diabetes. The main goal was to identify these fungi and evaluate their potential antibacterial properties. Samples of ironwood, including leaves and roots, were collected from the CV Nursery at Nusantara Asri, Cempaka Baru, Gunung Kupang, Banjarbaru, South Kalimantan, with coordinates -3.4892255, 114.8907642, 723. Using a series of steps—such as sterilizing samples, isolating fungi, conducting secondary metabolic fermentation, and testing for antimicrobial activity against Staphylococcus aureus and Escherichia coli—11 fungal isolates were successfully obtained from the plant's roots, leaves, and seeds. Five isolates were chosen for further study based on their growth rates, representing various genera including Cladosporium sp., Aspergillus sp., Mucor sp., and Hyphomycetes sp. Although the antimicrobial tests revealed that none of these isolates inhibited the bacteria, the results offer valuable insights into the interactions between these fungi and the bacterial strains tested.